جمالية اللغة في الشعر الشعبي الجزائري المعاصر: قراءة في الخيال الرمزي من خواطر على لميزي - العاقل، اليمين; بولنوار، علي (المركز الجامعي سي الحواس بريكة, 2023)
القصيدة الشعبية الجزائرية المعاصرة لون أدبي يعكس فيه الشاعر أحاسيسه ومشاعره، ويعبر فيه عن واقعه، لون له لغته الخاصة التي تميزه، تختلف عن لغة الشعر الفصيح، فهي وعاء حافظ للخطاب الشعري وأداة لتشكيل العمل الفني، تدرك بها حقيقة الشعر وتفهم مراميه، بتوظيفها حسب الغاية الجمالية التي يرمي لها الشاعر، لذا سنحاول في هذه الدراسة إبراز جمالية الأساليب اللغوية والأدوات الفنية التي وظفت بالمدونة (الخيال الرمزي من خواطر على لميزي)؛ من انزياح لغوي تركيبي، ونحوي، يظهر من خلال حالات التخفيف والتقديم والتأخير في الجملة، إضافة إلى ظاهرة التصغير، وكذلك توظيف الأساليب الإنشائية وما تحمله من دلالات جمالية فنية، وهذا دون إخلال بالمعنى العام للقصيدة. Contemporary Algerian folk poem is a literary color in which poets reflect their feelings and emotions, and describe their reality. This kind of poem has its own language that distinguishes it and makes it different from the language of eloquent poetry. It is a conservative aspect of the poetic discourse and a tool for shaping artwork by using it according to the aesthetic purpose of the poet. Therefore, this study aims to highlight the aesthetic linguistic styles, and artistic tools employed in the blog entitled Symbolic Fiction from Ali Laizi's thoughts from a synthetic linguistic and grammatical shift. The aesthetic linguistic styles appear through mitigation, initial and delays in the sentence, in addition to the miniaturization, and the use of structural methods and the implications of an artistic aesthetic, which occur without modifying the general meaning of the poem.
Keywords: الأعمال الفنية -- لغة الشعر -- الأساليب اللغوية -- الخيال الرمزي